A Profile of the Oil and Gas Industry, Second Edition : Resources, Market Forces, Geopolitics, and Technology. - Herkenhoff, Linda (Business Expert Press, 2018)
This book is a vital introduction to the oil and gas industry that focuses on history, operations, major companies, outside market forces, regulation, and the current challenges the industry faces. Such factors as finite natural resources, the environment, economics, geopolitics, and technology are also analyzed in detail. The focus on oil and gas is likely to continue to grow until efficient, environmentally safe alternate fuels become available. And because it's woven with complex relationships that are ever changing, this book is the best tool to have for a better understanding of this industry.